Reproduction and developmental stages in the crinoid Isometra vivipara Mortensen, 1917 from the southwestern Atlantic - Pertossi, Renata Micaela; Brogger, Martin Ignacio; Penchaszadeh, Pablo Enrique; Martinez, Mariano Ignacio (Polar Biology)
Isometra vivipara Mortensen, 1917, which was described one hundred years ago, represents a particular case within the feather stars of the southwestern Atlantic Ocean. This is a dioecious species in which the oocytes are fertilized in the ovary and not externally as in other species. Some authors have pointed out that I. vivipara stores spermatozoa in the genital pinnules of the female, although there is still no detailed data on how they reach the pinnule. Besides, this species is characterized by possessing a second sexually dimorphic trait and presents two incubation stages: one in the genital pinnules, and the second one attached in the cirri of the mother. In the present work, the reproduction and developmental stages of the I. vivipara were studied. Samples were taken from two cruises aboard the B/O “Puerto Deseado” to Burdwood Bank/MPA Namuncurá at 84–642 m depth, during March/April 2016 and April/May 2017. Four developmental stages were recognized: Embryo, Doliolaria larvae (inside the brood pouches), Cystidean, and Pentacrinoids (attached in the cirri of the mother). In addition, histological analysis showed that fertilization in I. vivipara could occur between the ovary and the marsupium. The egg measurements reached 0.35 mm in diameter—on of the largest egg size within South America and Antarctica comatulids—whereas for the larvae the largest registered diameter was 0.77 mm. These results are compared and discussed with all the available information of comatulids from South America and Antarctica. Fil: Pertossi, Renata Micaela. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Brogger, Martin Ignacio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina Fil: Penchaszadeh, Pablo Enrique. Consejo Nacional de Investigaciones ...